Detection of Listeria monocytogenes in Raw and Imported UHT Milk in Baghdad: Ali H.A. AL-Shamary ;Najim H. Najim - AL-Shamary, Ali H.A. (The Iraqi Journal of Veterinary Medicine, 2009)
In order to investigate the presence of Listeria monocytogenes in raw and imported Ultra Heat Treatment(UHT) milk, this study was done by random collection of samples from different areas in Baghdad province andits surroundings from different animals (small and large ruminants) as 68 total samples (53 raw milk samples and15 imported UHT samples)collected weekly from October 2007 till January 2008, and processed according tostandard protocols of Listeria monocytogenes .The results showed reisolation of 10 isolates from 68 samples (14.7%) as 6 isolated from raw milk samples(11.3%) and 4 isolated from UHT milk samples (26.7%) ,these revealed significant differences (P≤0.05) inisolated percentage of Listeria monocytogenes from raw milk of Cows, Buffalos , Ewes and Does especiallyfrom Al-Fadhyllea region , the highest isolation percentage was in November (2007) as 16.7%(3 isolates from 18samples ) especially from ewes as 1 isolate from 3 samples (33.4%) followed by cows and buffaloes with nonisolatesfrom Does .The percentage of isolation from UHT milk samples was 26.7% as 2 isolates from white UHT milk samples(40%) and 2 isolates from 10 chocolate UHT milk samples (20%).We concluded from this study by contamination of raw and imported UHT milk samples by Listeriamonocytogenes in Baghdad.